Effectiveness Of Mathematic Learning Media Based On Mobile Learning In Improving Student Learning Motivation - A. Muhajir Nasir; Nirfayanti Nirfayanti (Universitas Negeri Makassar, 2019)
This study aims to determine the effectiveness of the use of mobile learning based learning media on students' learning motivation in the Mathematics Education Study Program FKIP Maros Muslim University. The type of research used in this research was quantitative research with an experimental approach with the research subject being Mathematics Education Study Program students who are taking basic geometry courses in the even semester 2018/2019. The research design used was one group pretest-posttest design. Data was collected through tests and motivational questionnaires. The initial data analysis is used to check the normality of the data. The final analysis used the one sample t-test and normalized n-gain test. The results showed that the average normalized gain of student mathematics learning motivation was in the medium category and there was an increase in student learning motivation after being taught by applying the use of mobile learning in basic geometry learning